RETROSPECTIVE ANALYSIS OF PRIMARY FORENSIC MEDICAL EXAMINATIONS OF THE LOWER EXTREMITIES MECHANICAL TRAUMA - Sokol, V.K.; Kolesnichenko, V.A.; Protsenko, O.S. (World of Medicine and Biology, 2020)
The purpose of the study was to perform a retrospective analysis of primary forensic medical examinations that established moderate severity of bodily injuries in victims with mechanical injuries of lower extremities. The study revealed the predominance of road traffic injuries (92%); 8% were falls from the own height. Road traffic injuries were characterized by a predominance of people at working age (73%); vehicle hitting a pedestrian (86%); getting injured with polytrauma (82%); formation of diaphyseal fractures of the thigh and shin (78%); the presence of comorbid diseases (61%). The authors consider it necessary to revise the existing and to substantiate new medical criteria for determining the severity of bodily injury, taking into account the features of connective and muscle tissues reparative regeneration.
Keywords: mechanical trauma of the lower extremities; forensic medical examination; fractures of long bones; road traffic injury